Analisis Sumber dan Media Pembelajaran terhadap Pencapaian Tujuan Pembelajaran IPS di Sekolah Dasar - Rahma Syafitri, Novia; Ananda, Rizki; Rizal, M. Syahrul; Fitra Surya, Yenni; Mufarizuddin, Mufarizuddin (Universitas Nusantara PGRI Kediri, 2024)
The background of research is that existing learning resources and media have not been utilized optimally as seen from the use of learning resources that only focus on textbooks, lack of interaction and social attitudes in the learning process, lack of utilization of learning media, and students not focusing on participating in learning which causes social studies learning outcomes low. This study aims to describe the availability, utilization, school support and teacher constraints in using learning resources and media towards achieving social studies learning objectives at UPT Elementary Schools. Research using qualitative methods with a descriptive approach. The samples are school principals, high-grade social studies teachers and 6 students from each class. The results of the study show that the availability of learning resources and media is quite good and teachers can make good use of learning resources and media in the social studies learning process. There are obstacles to the use of learning resources and media in achieving social studies learning objectives in elementary schools such as requiring more time and a lack of reading books which make social studies learning objectives not optimally achieved, besides that school support from resource facilities and learning media is quite good. In conclusion, the availability and utilization of learning resources and media as well as school support for achieving social studies learning objectives is quite good and the obstacles encountered can be overcome properly in elementary schools